Pauulu's Diaspora Black Internationalism and Environmental Justice - Swan, Quito J. (University Press of Florida, 2020)
Pauulu's Diaspora is a sweeping story of black internationalism across the Atlantic, Indian, and Pacific Ocean worlds, told through the life and work of twentieth-century environmental activist Pauulu Kamarakafego. Challenging U.S.-centered views of Black Power, Quito Swan offers a radically broader perspective, showing how Kamarakafego helped connect liberation efforts of the African diaspora throughout the Global South. Born in Bermuda and with formative experiences in Cuba, Kamarakafego was aware at an early age of the effects of colonialism and the international scope of racism and segregation. After pursuing graduate studies in ecological engineering, he traveled to Africa, where he was inspired by the continent's independence struggles and contributed to various sustainable development movements. Swan explores Kamarakafego's remarkable fusion of political agitation and scientific expertise and traces his emergence as a central coordinator of major black internationalist conferences. Despite government surveillance, Kamarakafego built a network of black organizers that reached from Kenya to the islands of Oceania and included such figures as C. L. R. James, Queen Mother Audley Moore, Kwame Nkrumah, Sonia Sanchez, Sylvia Hill, Malcolm X, Vanessa Griffen, and Stokely Carmichael. In a riveting narrative that runs through Caribbean sugarcane fields, Liberian rubber plantations, and Papua New Guinean rainforests, Pauulu's Diaspora recognizes a global leader who has largely been absent from scholarship. In doing so, it brings to light little-known relationships among Black Power, pan-Africanism, and environmental justice.